BIOREMEDIATION OF CEMENT MINING WASTE AS A MEDIUM FOR GROWTH AND PRODUCTION OF CHILIES WITH MYCORRHIZA AND BIOHUMATE APPLICATION - Iradhatullah Rahim (Journal of Agriculture, 2023)
Cement mining by exploiting Maros karst, South Sulawesi, produces waste in the form of gypsum, which still has the potential to be used in bioremediation as a planting medium for plant commodities. The research aims to determine the growth of chili plants on former cement mining media treated with mycorrhiza and biohumic—the biohumate used from an extract of cocoa pod husk. The research was structured using an experimental method with 5 treatments, namely primary media in the form of soil + manure as a control, gypsum 30 g/polybag, gypsum 60 g/polybag, gypsum 30 g/polybag+mycorrhiza, gypsum 60 g/polybag+mycorrhiza. The treatment was then divided into 2, with biohumic and without biohumic. The research showed that all observed parameters had higher values in the biohumic treatment than without biohumic. Treatment with 30 g gypsum/polybag + mycorrhiza can improve the physical properties of the soil by changing the percentage composition of soil fractions. It can also increase P2O2 and K2O levels and provide the best growth for chili plants. It is possible to utilize waste from cement mines to produce horticultural commodities by bioremediation with mycorrhiza and biohumate.